2016
DOI: 10.1038/onc.2016.403
|View full text |Cite
|
Sign up to set email alerts
|

HSP110 promotes colorectal cancer growth through STAT3 activation

Abstract: Heat shock protein 110 (HSP110) is induced by different stresses and, through its anti-apoptotic and chaperoning properties, helps cells survive these adverse situations. In colon cancers, HSP110 is abnormally abundant. We have recently shown that colorectal cancer patients with microsatellite instability (MSI) had an improved response to chemotherapy because they harbor an HSP110-inactivating mutation (HSP110DE9). In this work, we used patient biopsies, human colorectal cancer cells grown in vitro and in vivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 26 publications
2
59
0
Order By: Relevance
“…Last, STAT3 is a well-documented regulator of cell growth, albeit more frequently having a positive effect. STAT3 has been associated with proliferative activity in numerous malignancies, including glioblastoma [59], non-small cell lung [60], and colorectal cancer [61]. In addition, STAT3-induced tumorigenesis is linked to its constitutive activity in certain cancer cells [6264].…”
Section: Discussionmentioning
confidence: 99%
“…Last, STAT3 is a well-documented regulator of cell growth, albeit more frequently having a positive effect. STAT3 has been associated with proliferative activity in numerous malignancies, including glioblastoma [59], non-small cell lung [60], and colorectal cancer [61]. In addition, STAT3-induced tumorigenesis is linked to its constitutive activity in certain cancer cells [6264].…”
Section: Discussionmentioning
confidence: 99%
“…It is also known that HSP110 overexpression is associated with nodal metastasis and an advanced stage in CRCs . According to a recent experimental study, HSP110 promotes the proliferation of colon cancer cells by directly activating STAT3 . Another recent study revealed that the HSP110 expression status is associated with differential polarization of tumor‐associated macrophages in colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…BCL‐2‐associated athanogene (BAG) family is a group of six NEFs reported to regulate Hsp70 function either positively or negatively. A member of NEFs is Hsp110 or Hsp70‐binding protein 1 that increases cell survival through antiapoptotic properties . (c) The tetratricopeptide repeat co‐chaperones, including Hop and CHIP, bind to the C‐terminal EEVD motif.…”
Section: Hsp70 Isoforms and Structurementioning
confidence: 99%